Educational technology - Aquino, Gaudencio V.; Razon, Perpetua U. (Manila, Philippines : Rex Book Store, 1993)
Educational psychology is sometimes referred to as the empirical foundation of education. This means that it represents those aspects of education that can be verified by experimentation, testing, and observation.
Chapter 1. Educational psychology: scope and functions -- Chapter 2. The Process of growth and development -- Chapter 3. Growth and development during infancy and childhood -- Chapter 4. Growth and development during adolescence -- Chapter 5. Individual differences -- Chapter 6. The Nature and types of learning -- Chapter 7. Theories of learning -- Chapter 8. Motivation and learning -- Chapter 9. Transfer of learning -- Chapter 10. Efficient learning -- Chapter 11. Concept formation and the development of thinking -- Chapter 12.The Learning of attitudes, values and skills -- Chapter 13. Handling behavioral problem children -- Chapter 14. Guidance and counseling in the schools -- Chapter 15. Measurement and evaluation -- Chapter 16. Statistical methods in education -- Chapter 17. The professional growth of the teacher -- Chapter 18. The Teacher's personality adjustment.
Includes index.
Keywords: EDUCATION